Infrasound Signal Detection and Back Azimuth Estimation Using Ground‐Coupled Airwaves on a Seismo‐Acoustic Sensor Pair. Issue 8 (22nd August 2018) - McKee, Kathleen; Fee, David; Haney, Matthew; Matoza, Robin S.; Lyons, John
Abstract: We present a new infrasonic signal detection and back azimuth determination technique that requires just one microphone and one three‐component seismometer. Ground‐coupled airwaves (GCAs) occur when an incident atmospheric acoustic wave impinges on the ground surface and is partially transmitted as a seismic wave. GCAs are commonly detected hundreds of kilometers away on seismic networks and are observed to have retrograde particle motion. Horizontally propagating acoustic waves and GCAs have previously been observed on collocated infrasound and seismic sensor pairs as coherent with a 90° phase difference. If the sensors are spatially separated, an additional propagation‐induced phase shift is present. The additional phase shift depends on the direction from which the acoustic wave arrives, as each back azimuth has a different apparent distance between the sensors. We use the additional phase shift, the coherence, and the characteristic particle motion on the three‐component seismometer to determine GCA arrivals and their unique back azimuth. We test this technique with synthetic seismo‐acoustic data generated by a coupled Earth‐atmosphere 3‐D finite difference code, as well as three seismo‐acoustic data sets from Mount St. Helens, Mount Cleveland, and Mount Pagan volcanoes. Results from our technique compare favorably with traditional infrasound array processing and provide robust GCA detection and back azimuth determination. Assuming adequate station spacing and sampling, our technique provides a new and robust method to detect infrasonic signals and determine their back azimuth, and may be of practical benefit where resources are limited and large sensor networks or arrays are not feasible. Key Points: We present a method to use a nearly co‐located seismic and acoustic sensor to detect acoustic waves and determine a unique back azimuth Application of our method to synthetic and recorded data produces back azimuth results similar to traditional array processing Successful application of this method requires adequate sensor separation, sample rate, and a three‐component seismometer